Asset Prices in Dynamic Production Economies with Time-Varying Risk - Naik, Vasanttilak (Review of Financial Studies, 1994)
Journal Article Asset Prices in Dynamic Production Economies with Time-Varying Risk Get access Vasanttilak Naik Vasanttilak Naik University of British Columbia Address correspondence to V. Naik, 2053 Main Mall, Faculty of Commerce and Business Administration, University of British Columbia, Vancouver, B.C., Canada V6T 1Z2. Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 7, Issue 4, October 1994, Pages 781–801, https://doi.org/10.1093/rfs/7.4.781 Published: 26 May 2015